Soil physical quality on black beans yield in an Alfisol - Collares, Gilberto Loguércio; Reinert, Dalvan José; Reichert, José Miguel; Kaiser, Douglas Rodrigo (Pesquisa Agropecuaria Brasileira, 2006)
In this work, soil properties and least limiting water range (LLWR) were determined for an Alfisol under three states of compaction with black beans crop. Three experiments were used, comprising the following treatments: 12 years of no-tillage NT; 12 years, of no-tillage compacted by four passes of a bucket loader NTc; and chiseling of soil previously under no-tillage for 12 years Ch. Throughout the plant cycle, bulk density, total porosity, volumetric water content, air filled porosity and soil resistance to penetration were evaluated. Plant root distribution and yield were also evaluated. The critical bulk density obtained by LLWR was 1.75 Mg m-3. In the NTc the bulk density was higher than critical value for most soil layers, whereas the PD and Ch presented higher value in a few layers. Soil water content was out of LLWR range for most part of plant cycle. Soil resistance to penetration in the NTc was higher than critical value in all evaluated dates, while in roots concentrated superficially. For the three experiments, higher compaction levels (NTc) induced yield reduction from 30 to 62% and soil chiseling (Ch) induced yield reduction from 2 to 12% compared to crops under no-tillage (PD). Compaction alleviation by chiseling was not necessary to improve crop yield for soil physical conditions of this area.